O perfil do aluno de cursos técnicos ou Parem as máquinas: o aluno envelheceu - Motta, Paulo Tadeu Rabelo da [UNESP] (My University, 2014)
The enrollments in technical courses outgrew beyond 70% between 2002 and 2010. It has made fundamental to look after this educational segment because of the changes in the job market, associated with the promulgation of the Law #11.741, witch disentails the High Scholl from the Professional Education, points out to some better understanding of this population. This study intended to trace the profile of this student. The socioeconomic criteria by Abipeme (Brazilian Association of Market Research Institutes) was used, and the most important item was age, with a result higher than expected to this educational phase, about 24 years old. The respondents characterized themselves as pertaining to B and C economical classes.

As matrículas nos cursos técnicos cresceram para além dos 70%, entre 2002 e 2010. Tornou-se fundamental voltarmos o olhar para esse segmento educacional, pois as mudanças no mercado de trabalho, aliadas à promulgação da Lei nº 11.741, que desvincula o Ensino Médio da Educação Profissional, apontam para uma melhor compreensão dessa população. O objetivo do presente estudo foi traçar um perfil desse aluno. Utilizamos o critério socioeconômico da Abipeme (Associação Brasileira de Institutos de Pesquisa de Mercado), e o item que mais se destacou foi a idade, que se apresentou muito superior à média esperada para essa fase educacional, em torno de 24 anos. Os respondentes caracterizam-se por pertencerem às classes socioeconômicas B e C.
The profile of technical courses student or Stop the machines: the student got old
Keywords: Technical schools; Technical teaching; Professional teaching; Escolas técnicas; Ensino técnico; Ensino profissional